Addressing the Increase of Domestic Violence and Abuse During the COVID-19 Pandemic: A Need for Empathy, Care, and Social Equity in Collaborative Planning and Responses. Issue 6 (August 2020) - Rauhaus, Beth M.; Sibila, Deborah; Johnson, Andrew F.
During COVID-19, stay at home orders have led to the rise of domestic violence and abuse claims in many localities globally, leaving community leaders unprepared to address the increase of domestic violence incidences. As local public officials are becoming concerned about the increase of domestic violence and in some instances, the decrease due to the inability of victims to report instances, a collaborative response is necessary. This work examines how social equity and public service values, such as compassion, empathy, and an ethic of care, may be incorporated into collaborative planning and responses to domestic violence plaguing communities during the pandemic. Recommendations for raising awareness, incorporating social equity in public service, and collaborative reporting are made.